Dendritic Packing and Porosity Formation within Single Crystal CMSX-4® Ni-Base Superalloy. Issue 1 (September 2020) - Perry, S; Strickland, J; Nenchev, B; Tassenberg, K; Dong, HB
Abstract: Specialised imaging techniques are instrumental for extracting the wealth of information locked within as-cast microstructures. Recently, a novel characterisation tool (Shape-Limited Primary Spacing) was developed for determining primary dendrite arm spacing (PDAS), dendritic packing pattern and porosity formation within single crystal microstructures. In this work, the algorithm is applied to a single crystal CMSX-4® Ni-base superalloy to investigate the relationship between dendritic packing pattern and condensation porosity. It is concluded that porosity formation is reduced when regular organised dendritic packing patterns form. This work elucidates new unknown relationships between packing and porosity and may help to develop improved process-property models for defect prediction.